Extreme value distributions : theory and applications - Kotz, Samuel (Imperial College Press ; Distributed by World Scientific, 2000)
This important book provides an up-to-date comprehensive and down-to-earth survey of the theory and practice of extreme value distributions -- one of the most prominent success stories of modern applied probability and statistics. Originated by E J Gumbel in the early forties as a tool for predicting floods, extreme value distributions evolved during the last 50 years into a coherent theory with applications in practically all fields of human endeavor where maximal or minimal values (the so-called extremes) are of relevance. The book is of usefulness both for a beginner with a limited probabilistic background and to expert in the field.